Defects and charge transport in Mn-doped K0.5Na0.5NbO3 ceramics. Issue 37 (7th October 2015) - Rafiq, Muhammad Asif; Tkach, Alexander; Costa, Maria Elisabete; Vilarinho, Paula Maria
<x xml:space="preserve">Abstract</x> KNN room-temperature conduction is associated with hole transport and can be suppressed by Mn-doping; a less leaky hysteresis loop is obtained. At high temperatures conduction is dominated by ionized oxygen vacancies motion. From grains and grain-boundaries resistance oxygen vacancies in KNN and Mn-doped KNN ceramics are mainly located at grain-boundaries.